Significance of levothyroxine treatment on serum lipid in pregnant women with subclinical hypothyroidism - Yuxi Yang; Huabing Yuan; Xueran Wang; Zheng Zhang; Ruixia Liu; Chenghong Yin (BMC, 2022)
Abstract Background There is no consensus reference range for serum lipid levels during pregnancy. The benefit of levothyroxine (L-T4) on serum lipid levels are unclear among pregnant women with subclinical hypothyroidism (SCH). Objective To determine the recommended reference ranges for serum lipid concentrations during pregnancy and effects of L-T4 treatment on serum lipids in pregnant women with SCH. Design Cohort study. Methods A analysis of 20,365 women in the first trimester was conducted at Beijing Obstetrics and Gynecology Hospital, Capital Medical University during 2018-2020. After excluding women with adverse pregnancy outcomes, we determined the reference range of serum lipid in the first and third trimesters of pregnancy by using median and quartile to determine appropriate percentiles. Next, we divided into three groups as follows: SCH L-T4 treatment group (n = 319), SCH non-intervention group (n = 103) and the control group(n = 9598). Results The recommended reference range for serum lipids in the first trimester of pregnancy should be: TC < 5.33 mmol/L, TG < 1.73 mmol/L, LDL-C < 3.12 mmol/L and HDL-C > 1.1 mmol/L, and in third trimester of pregnancy should be: TC < 8.47 mmol/L, TG < 4.86 mmol/L, LDL-C < 5.3 mmol/L and HDL-C > 1.34 mmol/L. There are significant differences in TC and LDL-C levels between SCH treatment group and SCH non-intervention Group (P = 0.043, P = 0.046; respectively). Conclusions We determine the recommended reference ranges for serum lipid concentrations during pregnancy. TC and LDL-C levels in pregnant women with SCH could improve after L-T4 treatment.